2003
DOI: 10.1136/bjo.87.3.330
|View full text |Cite
|
Sign up to set email alerts
|

High resolution magnetic resonance imaging of retinoblastoma

Abstract: Background/aims: Diagnosis of retinoblastoma is mainly based on indirect ophthalmoscopy, but additional imaging techniques are indispensable for the staging of the disease. A new high resolution magnetic resonance imaging (MRI) technique for the examination of the eye was evaluated. A new surface coil with a diameter of 5 cm allows a field of view of 60 mm with an in-plane resolution of 0.8 mm. We compared preoperative MRI scans with the histology after enucleation in 21 cases of retinoblastoma. Parameters stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 23 publications
1
52
0
10
Order By: Relevance
“…MR imaging is the method of choice in depicting ocular lesions; 8,11,[25][26][27] however, CT is still the method of choice for detecting intraocular calcium and investigating orbital pathologies. 28,29 The disadvantages of CT are reduced soft-tissue contrast and spatial resolution compared with MR imaging; the presence of the potential risk of iodinated contrast administration; and radiation exposure, especially in those patients with the hereditary form of the disease, who have elevated radiosensitivity.…”
Section: Correspondence Between Signal-void Spots On Mr Imaging and Cmentioning
confidence: 99%
See 1 more Smart Citation
“…MR imaging is the method of choice in depicting ocular lesions; 8,11,[25][26][27] however, CT is still the method of choice for detecting intraocular calcium and investigating orbital pathologies. 28,29 The disadvantages of CT are reduced soft-tissue contrast and spatial resolution compared with MR imaging; the presence of the potential risk of iodinated contrast administration; and radiation exposure, especially in those patients with the hereditary form of the disease, who have elevated radiosensitivity.…”
Section: Correspondence Between Signal-void Spots On Mr Imaging and Cmentioning
confidence: 99%
“…The development of a smaller diameter dedicated surface coil may allow the detection of very small intraocular lesions, even with a thickness of Ͻ1 mm. 27 Our study has clearly shown the possibility of detecting calcifications in retinoblastoma, when MR imaging, ultrasonographic, and ophthalmoscopic data are used jointly.…”
mentioning
confidence: 99%
“…Currently, the use of orbital surface coils is recommended for retinoblastoma imaging to increase spatial resolution and signal-to-noise ratio. 5,7 Future research on retinoblastoma-associated BOB impairment and quantification of leakage across the endothelium should be performed with dynamic contrast-enhanced MR imaging, which is widely used for tumor imaging. 33 Contrast-enhanced MR imaging seems to be a useful tool for noninvasive detection of retinoblastoma-related angiogenesis and could define a subgroup of patients who would potentially profit from vascular targeting drugs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] MR imaging provides the opportunity for a noninvasive evaluation of these risk factors with reasonable diagnostic accuracy. [5][6][7][8] Tumor angiogenesis is also a histopathologic risk factor for local tumor invasion and systemic dissemination in retinoblastoma 9,10 ; initial reports on vascular targeting therapy in mouse models of retinoblastoma show promising results. 11 However, evaluation of angiogenic activity has been performed only in vitro on the histopathology of enucleated eyes.…”
mentioning
confidence: 99%
“…These characteristics can be well-detected on histopathology, but detection by conventional MR imaging is not optimal so far. [5][6][7][8][9][10][11][12][13] Therefore, it is important to assess the prospects of other MR imaging methods that could further optimize the tumor tissue characterization in vivo.…”
mentioning
confidence: 99%